Human monkeypox – After 40 years, an unintended consequence of smallpox eradication. Issue 33 (14th July 2020) - Simpson, Karl; Heymann, David; Brown, Colin S.; Edmunds, W. John; Elsgaard, Jesper; Fine, Paul; Hochrein, Hubertus; Hoff, Nicole A.; Green, Andrew; Ihekweazu, Chikwe; Jones, Terry C.; Lule, Swaib; et al.
Highlights: 40 years after smallpox eradication, monkeypox is a human disease. 2018–19 export of monkeypox from Nigeria to the UK, Israel and Singapore. Monkeypox epidemiology needs more study. Human monkeypox, an unintended consequence of smallpox eradication. Other orthopox viruses, a threat to animal and human health. Abstract: Smallpox eradication, coordinated by the WHO and certified 40 years ago, led to the cessation of routine smallpox vaccination in most countries. It is estimated that over 70% of the world's population is no longer protected against smallpox, and through cross-immunity, to closely related orthopox viruses such as monkeypox. Monkeypox is now a re-emerging disease. Monkeypox is endemic in as yet unconfirmed animal reservoirs in sub-Saharan Africa, while its human epidemiology appears to be changing. Monkeypox in small animals imported from Ghana as exotic pets was at the origin of an outbreak of human monkeypox in the USA in 2003. Travellers infected in Nigeria were at the origin of monkeypox cases in the UK in 2018 and 2019, Israel in 2018 and Singapore in2019. Together with sporadic reports of human infections with other orthopox viruses, these facts invite speculation that emergent or re-emergent human monkeypox might fill the epidemiological niche vacated by smallpox. An ad-hoc and unofficial group of interested experts met to consider these issues at Chatham House, London in June 2019, in order to review available data and identify monkeypox-related research gaps. Gaps identified by the experts included: understanding of zoonotic hosts, reservoirs and vectors. risks associated with transmission. full description of the clinical spectrum and the natural history of infection including an estimation of the prevalence of monkeypox specific antibodies in humans living in areas of emergence. The experts further agreed on the need for a better understanding of the genomic evolution and changing epidemiology of orthopox viruses, the usefulness of in-field genomic diagnostics, and the best disease control strategies, including the possibility of vaccination with new generation non-replicating smallpox vaccines and treatment with recently developed antivirals.